Land use/land cover change as a major driver of current landscape flammability in Eastern Mediterranean region: A case study in Southwestern Turkey - Coskuner, Kadir Alperen (BOSQUE, 2022)
Land use/land cover (LULC) change has been one of the main drivers of landscape changes in the Mediterranean region where there has been an increase in the forested lands. LULC change in the region has not only changed forest stand structure and composition but also resulted in increase in the available combustible fuels. There have been few studies on fuel accumulation in relation to LULC, however, no study explaining quantitatively the relationship between LULC change and canopy fuel load in the Mediterranean region. The objective of this study is to evaluate the effects of LULC changes on overall crown fire hazard through examining stand structure, composition, and canopy fuel loads in Eastern Mediterranean forests for 35 years. Forest stand type maps generated from the stereo interpretation of aerial photographs and field survey data were used for the analyses. The results of the study showed significant changes in LULC during the period of 1977-2012. There was a 16.6 % decrease in agricultural areas, 144.5 % increase in settlement areas and 6.8 % increase in pine forests. As for the structural and compositional changes in forested lands, open pine stands that included Mediterranean shrub communities decreased (77.2 %); nonetheless, closed pure pine stands increased (49.9 %), resulting in an increase in the total canopy fuel load in pine stands (86.4 %). Results indicated that landscapes tended to become more homogeneous, fully closed pine stands, resulting in an increase in the continuity and the buildup of fuels available for combustion.